INdividual Vocational and Educational Support Trial (INVEST) for young people with borderline personality disorder: study protocol for a randomised controlled trial - Andrew M. Chanen; Katie Nicol; Jennifer K. Betts; Gary R. Bond; Cathrine Mihalopoulos; Henry J. Jackson; Katherine N. Thompson; Martina Jovev; Hok Pan Yuen; Gina Chinnery; Judith Ring; Kelly Allott; et al. (Trials, 2020)
Abstract Background The clinical onset of borderline personality disorder (BPD) usually occurs in young people (aged 12–25 years) and commonly leads to difficulty achieving and maintaining vocational (education and/or employment) engagement. While current psychosocial interventions lead to improvements in psychopathology, they have little effect upon functioning. Individual Placement and Support (IPS) is a client-driven model that assists individuals with severe mental illness to engage with education and/or employment appropriate to their personal goals, and that provides ongoing support to maintain this engagement. The objective of the INdividual Vocational and Educational Support Trial (INVEST) is to evaluate the effectiveness of adding IPS to an evidence-based early intervention programme for BPD, with the aim of improving vocational outcomes. Methods/design INVEST is a single-blind, parallel-groups, randomised controlled trial (RCT). The randomisation is stratified by gender and age and uses random permuted blocks. The interventions are 39 weeks of either IPS, or ‘usual vocational services’ (UVS). Participants will comprise 108 help-seeking young people (aged 15–25 years) with three or more DSM-5 BPD features and a desire to study or work, recruited from the Helping Young People Early (HYPE) early intervention programme for BPD at Orygen, in Melbourne, Australia. All participants will receive the HYPE intervention. After baseline assessment, staff who are blind to the intervention group allocation will conduct assessments at 13, 26, 39 and 52 weeks. At the 52-week primary endpoint, the primary outcome is the number of days in mainstream education/employment since baseline. Secondary outcomes include the cost-effectiveness of the intervention, quality of life, and BPD severity. Discussion Current treatments for BPD have little impact on vocational outcomes and enduring functional impairment is prevalent among this patient group. IPS is a targeted functional intervention, which has proven effective in improving vocational outcomes for adults and young people with psychotic disorders. This trial will investigate whether IPS is effective for improving vocational (employment and educational) outcomes among young people with subthreshold or full-syndrome BPD. Trial registration Australian New Zealand Clinical Trials Registry, ID: ACTRN12619001220156 . 13 September 2019.